On estimating the regular normal cone to constraint systems and stationarity conditions. (2nd January 2017) - Benko, Matus; Gfrerer, Helmut
Abstract: Estimating the regular normal cone to constraint systems plays an important role for the derivation of sharp necessary optimality conditions. We present two novel approaches and introduce a new stationarity concept which is stronger than M-stationarity. We apply our theory to three classes of mathematical programs frequently arising in the literature.